Case Study: Successful Design of Local Products that Go International - Alaa Chahine; Nina Anis; pong Krit (Journal of Loomingulisus ja Innovatsioon, 2026)
This case study explores the successful design of local products that have achieved international recognition. In a globalized economy, many local products face significant challenges in entering international markets, often requiring strategic design innovation to compete. The importance of culturally relevant, functional, and aesthetically appealing designs has become essential for products aiming for international expansion. This research aims to identify the key factors that contribute to the success of local products in gaining international market share through effective product design. The objective of the study is to examine the role of product design in overcoming the barriers faced by local products in global markets, focusing on case studies of brands that have successfully navigated this process. The research employs a qualitative case study methodology, analyzing in-depth interviews with designers, product managers, and international marketing experts, as well as reviewing secondary data from product sales and market reports. The findings reveal that successful local products incorporated unique design elements that resonated with global consumer preferences while retaining local cultural identity. Moreover, product functionality and adaptability to different market needs were crucial in facilitating international success. Strategic marketing and branding also played significant roles in enhancing the global appeal of these products. In conclusion, local products that successfully transition to international markets do so by aligning their design with global trends while maintaining authenticity. This case study offers valuable insights for businesses seeking to expand their product designs beyond local borders.